2004
DOI: 10.1074/jbc.m313941200
|View full text |Cite
|
Sign up to set email alerts
|

Channel Gating of the Glycine Receptor Changes Accessibility to Residues Implicated in Receptor Potentiation by Alcohols and Anesthetics

Abstract: The glycine receptor is a target for both alcohols and anesthetics, and certain amino acids in the ␣1 subunit transmembrane segments (TM) are critical for drug effects. Introducing larger amino acids at these positions increases the potency of glycine, suggesting that introducing larger residues, or drug molecules, into the drugbinding cavity facilitates channel opening. A possible mechanism for these actions is that the volume of the cavity expands and contracts during channel opening and closing. To investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 42 publications
10
79
0
Order By: Relevance
“…Such a large potentiating effect is seen because PMTS, unlike volatile anesthetics, binds covalently and thus is always present when glycine binds to activate the receptor. A similarly large effect was previously observed with benzyl-MTS labeling of homomeric S267C GlyRs (22). In addition, our estimate of the maximal effect of glycine (EC 100 ) is likely an underestimate because drug perfusion in oocytes occurs slowly and considerable desensitization may have occurred before the current peak height was achieved.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Such a large potentiating effect is seen because PMTS, unlike volatile anesthetics, binds covalently and thus is always present when glycine binds to activate the receptor. A similarly large effect was previously observed with benzyl-MTS labeling of homomeric S267C GlyRs (22). In addition, our estimate of the maximal effect of glycine (EC 100 ) is likely an underestimate because drug perfusion in oocytes occurs slowly and considerable desensitization may have occurred before the current peak height was achieved.…”
Section: Discussionmentioning
confidence: 61%
“…Using the substituted cysteine accessibility method with homomeric cysteine mutants, Lobo et al (22) recently found that the GlyR alcohol and anesthetic binding pocket undergoes a conformational change upon receptor gating to the open state. This suggests that alcohol or anesthetic occupancy of the binding pocket promotes the open state by favoring an enlarged pocket conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in M1 have been shown to produce receptors that have altered desensitization, changes in EC 50 or are non-functional (Akabas & Karlin, 1995 ;Bianchi et al 2001 ;Dang et al 2000 ;Engblom et al 2002 ;England et al 1999 ;Greenfield et al 2002 ;Lobitz et al 2001 ;Lobo et al 2004 ;Spitzmaul et al 2004 ;Zhang & Karlin, 1997). M1 may therefore be a structural element involved in transmitting movement of the ligand-bound ECD into M2, possibly through direct interactions with the M2 helix following activation (Unwin et al 2002).…”
Section: (2009)mentioning
confidence: 99%
“…Propofol is an intravenous anesthetic that potentiates GlyRs by binding to the alcohol and anesthetic binding site located between TM2 and TM3 (26,27). Its potentiation, particularly of taurine-and ␤-alanine-gated currents, is facilitated by mutations to R19Ј in ␣1 GlyRs (28).…”
Section: Analysis Of the Effects Of The Glyr Potentiating Agent Propmentioning
confidence: 99%